Does the first hour of continuous electroencephalography predict neonatal seizures?. Issue 2 (14th September 2020) - Macdonald-Laurs, Emma; Sharpe, Cynthia; Nespeca, Mark; Rismanchi, Neggy; Gold, Jeffrey J; Kuperman, Rachel; Wang, Sonya; Lee, Ngoc Minh D; Michelson, David J; Haas, Richard; Reed, Peter; Davis, Suzanne L
Abstract : Objective: Prolonged continuous video-electroencephalography (cEEG) is recommended for neonates at risk of seizures. The cost and expertise required to provide a real-time response to detected seizures often limits its utility. We hypothesised that the first hour of cEEG could predict subsequent seizures. Design and setting: Retrospective multicentre diagnostic accuracy study. Patients: 266 term neonates at risk of seizure or with suspected seizures. Intervention: The first hour of cEEG was graded by expert and novice interpreters as normal, mildly, moderately or severely abnormal; seizures were identified. Main outcome measures: Association between abnormalities in the first hour of cEEG and the presence of seizures during total cEEG monitoring. Results: 50/98 (51%) of neonates who developed seizures had their first seizure in the first hour of cEEG monitoring. The 'time-to-event' risk of seizure from 0 to 96 hours was 0.38 (95% CI 0.32 to 0.44) while the risk in the first hour was 0.19 (95% CI 0.15 to 0.24). cEEG background was normal in 48% of neonates, mildly abnormal in 30%, moderately abnormal in 13% and severely abnormal in 9%. Inter-rater agreement for determination of background was very good (weighted kappa=0.81, 95% CI 0.72 to 0.91). When neonates with seizures during the first hour were excluded, an abnormal background resulted in 2.4 times increased risk of seizures during the subsequent monitoring period (95% CI 1.3 to 4.4, p<0.003) while a severely abnormal background resulted in a sevenfold increased risk (95% CI 3.4 to 14.3, p<0.0001). Conclusions: The first hour of cEEG in at-risk neonates is useful in identifying and predicting whether seizures occur during cEEG monitoring up to 96 hours. This finding enables identification of high-risk neonates who require closer observation.